2000
DOI: 10.1103/physrevc.61.051303
|View full text |Cite
|
Sign up to set email alerts
|

Three-body analysis of the occurrence of Efimov states in2nhalo nuclei such as19B,

Abstract: By employing separable potentials for the binary, i.e., n-n and n-core subsystems, we compute the threebody integral equations to solve for the 2n-separation energies in the ground and excited states of halo nuclei like 19 B, 22 C, and 20 C. We show through numerical analysis and also from analytical considerations that Borromean-type halo nuclei like 19 B and 22 C, where n-n and n-core are both unbound, are much less vulnerable to respond to the existence of the Efimov effect. On the contrary, those nuclei, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 10 publications
2
49
0
Order By: Relevance
“…The result for 11 Li, r 2 nn exp = (6.6 ± 1.5) fm, is in close agreement with both the LO, r 2 nn = (6.8 ± 1.8) fm, and NLO, r 2 nn = (6.3 ± 0.5) fm, calculations found using the two-body virtual energy reported in [48], E nc = −800 keV. However, due to the large uncertainties in both the theoretical and experimental values for 11 Li, there exists a large range of E nc values which would produce a r 2 nn value in agreement with the experimental value of Marqués et al [50]. The LO result for 14 Be, r 2 nn = (4.1 ± 0.5) fm, is about a Fermi below the the experimental value from Ref.…”
Section: B Range Corrections To 2n Halo Nuclei Mean Square Radiimentioning
confidence: 99%
See 1 more Smart Citation
“…The result for 11 Li, r 2 nn exp = (6.6 ± 1.5) fm, is in close agreement with both the LO, r 2 nn = (6.8 ± 1.8) fm, and NLO, r 2 nn = (6.3 ± 0.5) fm, calculations found using the two-body virtual energy reported in [48], E nc = −800 keV. However, due to the large uncertainties in both the theoretical and experimental values for 11 Li, there exists a large range of E nc values which would produce a r 2 nn value in agreement with the experimental value of Marqués et al [50]. The LO result for 14 Be, r 2 nn = (4.1 ± 0.5) fm, is about a Fermi below the the experimental value from Ref.…”
Section: B Range Corrections To 2n Halo Nuclei Mean Square Radiimentioning
confidence: 99%
“…For the Borromean halo nuclei 11 Li and 14 Be, in which all two-body subsystems are unbound, the general tendency is for a positive effective range to shift all mean square radii to smaller values. The only exception is the case of 11 Li using the central value of the n-c energy E nc = (−25 ± 15) keV [39].…”
Section: B Range Corrections To 2n Halo Nuclei Mean Square Radiimentioning
confidence: 99%
“…From the earliest studies of halo nuclei, 20 C has been suggested as a good candidate for Efimov states [18], with future theoretical work supporting this prediction [19,20]. We critically examine these earlier studies and perform an improved analysis in the framework of an effective theory.…”
Section: Introductionmentioning
confidence: 99%
“…III C, there possibly exists one Efimov excited state in 20 C for E nc < 165 keV. The mean square radii for this excited state were calculated over a range of E nc values and plotted, with leading order error bands, in Fig.…”
Section: B Mean Square Radii and Geometry Of 2n Halo Nucleimentioning
confidence: 99%
“…The properties of halo nuclei can be understood by treating the nucleus as an effective three body system consisting of a Core and two neutrons (Core-n-n) [4,[8][9][10] with the assumption that excitation energies of the core, E * core , are much larger than the other energy scales, E nn and E nc . It is found that the relative properties of the Efimov states can be expressed in terms of ratios (see for example Ref.…”
Section: Introductionmentioning
confidence: 99%